Universal behaviour of high-Q Fano resonances in metamaterials : terahertz to near-infrared regime - Lim, Wen Xiang (2019)
The observation of Fano resonance phenomena is universal across several branches of physics. Photonics is one of the most important areas of physics that mainly deals with the control of light propagation and localization through its interaction with natural and artificially engineered media. In an era of miniaturization, manipulation of light at micro-nanoscales has assumed unprecedented significance due to its potential to satisfy the mankind with disruptive future technologies. In this work, we present our study on the universality of high quality factor Fano resonances in planar metamaterials across terahertz and infrared parts of the electromagnetic spectrum. The narrow linewidth asymmetric Fano resonant metamaterials have tremendous potential to find applications in micro-nanoscale flat lasers, sensors, and ultra-resolution spectrometers.